Re-reading Room (Kuching Chinese Voices on Heritage) Exhibition 2025 - Nana, Zheng; Noria, Tugang; Auzani Zeda, Mohamed Kassim (2025)
his "Re-Reading Room" features two interconnected parts. The first part is the cave-shaped installation right in front of you. In creating this massive work, architect and artist Tay Tze Yong combined rigorous architectural engineering with his wild imagination of space and urban life. Paying tribute to the ancient tradition of co-creating art in caves, Tay invited people from different walks of life in Kuching to contribute their creativity to this work. This is why the installation is named "Echoes of Creation." The second part is the reading space we have curated for you. In this room, we invite you to re-read the Chinese communities of Kuching and their participation in heritage activities. Do you think of temples, festival parades, and Carpenter Street when you hear "Kuching Chinese"? Do you visualise traditional crafts, archaeological sites, and artefact conservation when you hear the word "heritage"? While you are absolutely right, this Re-Reading Room reveals much more than that. How are these two parts connected? During the installation's display at Hoan Gallery from June 8 to 19 August 2025, local Chinese associations, schools, and individuals were invited to participate in its co-creation. Some of their contributions reflect their perceptions of Chinese identity and what heritage means to them.